Oral sensory and motor skills in normals and a clinical population - K.C, Shyamala (Journal of All India Institute of Speech and Hearing)
A review of literature indicated controversial findings regarding the possible relationship between oral sensory-motor efficiency and speech proficiency. Hence the present study aimed at evaluating oral sensory and motor abilities on 64 subjects (30 normals, 24 stutterers and 10 subjects with misarticulations) within the age range of 13-25 years.